Layoffs, Recruitment, and Interfirm Mobility - Hosios, Arthur J. (Journal of Labor Economics, 1986)
Contract and search theories are integrated to provide a consistent explanation of contract formation, the intertemporal structure of labor markets, the absence of ex post market clearing, and thus of unemployment in a contractual setting. Self-fulfilling equilibria are described in which low-productivity firms lay off some workers, while high-productivity firms' recruitment (search) intensity and the resulting degree of interfirm mobility are endogenous. The effects of severance pay on layoffs and mobility are identified. Finally, the market economy is shown to generate too few layoffs whenever high-productivity firms recruit new hires: without recruitment, laidoff workers are immobile, and equilibrium is constrained efficient.